2011
DOI: 10.1371/journal.pone.0028491
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy Inhibition Enhances Daunorubicin-Induced Apoptosis in K562 Cells

Abstract: Anthracycline daunorubicin (DNR) is one of the major antitumor agents widely used in the treatment of myeloid leukemia. Unfortunately, the clinical efficacy of DNR was limited because of its cytotoxity at high dosage. As a novel cytoprotective mechanism for tumor cell to survive under unfavorable conditions, autophagy has been proposed to play a role in drug resistance of tumor cells. Whether DNR can activate to impair the sensitivity of cancer cells remains unknown. Here, we first report that DNR can induce a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
64
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(73 citation statements)
references
References 28 publications
8
64
1
Order By: Relevance
“…Our present study demonstrated that the levels of LC3-II and beclin 1 increased significantly after exposure to colistin (31.25 to 250 g/ ml), indicating that colistin treatment led to increased numbers of autophagosomes. Our result is in keeping with previous reports that autophagy preceded apoptosis under certain stress conditions (44)(45)(46). The evidence currently accumulating in the literature demonstrates that toxins and chemicals can activate autophagy and apoptosis and that the early autophagic response provides potential protection against the toxic effects (47-49).…”
Section: Discussionsupporting
confidence: 93%
“…Our present study demonstrated that the levels of LC3-II and beclin 1 increased significantly after exposure to colistin (31.25 to 250 g/ ml), indicating that colistin treatment led to increased numbers of autophagosomes. Our result is in keeping with previous reports that autophagy preceded apoptosis under certain stress conditions (44)(45)(46). The evidence currently accumulating in the literature demonstrates that toxins and chemicals can activate autophagy and apoptosis and that the early autophagic response provides potential protection against the toxic effects (47-49).…”
Section: Discussionsupporting
confidence: 93%
“…Akt and ERK activation likely plays a defensive role by restricting excessive toxicity, since cotreatment with pharmacological inhibitors of these kinases augments apoptosis or necrosis provoked by 3-BrP. Interestingly, the potentiation of apoptosis/necrosis by the MEK/ERK inhibitor might support the hypothesis of a role for defensive autophagy, since autophagy is normally positively regulated by MEK/ERK (Han et al, 2011;Davidescu et al, 2012). However, this hypothesis could not explain the potentiation of apoptosis or necrosis by the Akt inhibitor since the Akt/mTOR pathway commonly exerts negative regulation on the autophagic response (Wu et al, 2009;Davidescu et al, 2012).…”
Section: Discussionmentioning
confidence: 95%
“…In our experiments, 20-30 mM 3-BrP decreased ATP and induced mIMP, and preliminary observations also point to a decrease in p62/SQSTM1 levels (data not shown) that is a characteristic of autophagy. Because autophagy is considered a prosurvival response opposing apoptosis and necrosis (Wu et al, 2009;Han et al, 2011), an attractive possibility is that the intensity of apoptosis or necrosis in 3-BrP-treated AML cells is restrained by a concomitant autophagic response, a hypothesis that requires further study.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, pharmacological inhibition of autophagy increases the sensitivity of cancer cells to target therapy and chemotherapy. 22,23 Therefore, transformed cancer cells utilize autophagy predominantly as a survival mechanism to sustain viability under unfavorable conditions. Indeed, autophagy in primary tumors primarily localizes to less-perfused regions with limited oxygen and nutrients.…”
Section: Mir372mentioning
confidence: 99%
“…Meanwhile, blocking autophagy with either the lysosomal inhibitor chloroquine or ATG7 siRNAs strongly enhances the apoptosis induced by various anticancer agents such as tyrosine kinase inhibitors. [20][21][22][23] SQSTM1, a member of the autophagic receptors that promote autophagy activation, is highly expressed in many human cancers. [24][25][26] In addition, accumulation of SQSTM1 promotes tumorigenesis while inhibition of autophagy prevents tumor growth in nude mice.…”
Section: Introductionmentioning
confidence: 99%